2020
DOI: 10.1186/s13068-020-01688-x
|View full text |Cite
|
Sign up to set email alerts
|

Lipase immobilized on functionalized superparamagnetic few-layer graphene oxide as an efficient nanobiocatalyst for biodiesel production from Chlorella vulgaris bio-oil

Abstract: Background: Microalgae, due to its well-recognized advantages have gained renewed interest as potentially good feedstock for biodiesel. Production of fatty acid methyl esters (FAMEs) as a type of biodiesel was carried out from Chlorella vulgaris bio-oil. Biodiesel was produced in the presence of nano-biocatalysts composed of immobilized lipase on functionalized superparamagnetic few-layer graphene oxide via a transesterification reaction. A hybrid of few-layer graphene oxide and Fe 3 O 4 (MGO) was prepared and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(26 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…In any case, there are several studies that employ this immobilisation technique in biodiesel synthesis. Nematian et al [213] immobilised proROL onto a superparamagnetic nanostructure and described that amongst the three different biocatalysts studied-two based on lipase-support electrostatic interactions and the third one on covalent-linkage-the covalently immobilised proROL showed higher conversion and operational stability. Bonet-Ragel et al [181] covalently immobilised rROL onto glutaraldehyde pre-treated epoxide acrylic resins and studied its reaction performance and operational stability in biodiesel synthesis with methanol and ethanol as acyl-acceptors.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…In any case, there are several studies that employ this immobilisation technique in biodiesel synthesis. Nematian et al [213] immobilised proROL onto a superparamagnetic nanostructure and described that amongst the three different biocatalysts studied-two based on lipase-support electrostatic interactions and the third one on covalent-linkage-the covalently immobilised proROL showed higher conversion and operational stability. Bonet-Ragel et al [181] covalently immobilised rROL onto glutaraldehyde pre-treated epoxide acrylic resins and studied its reaction performance and operational stability in biodiesel synthesis with methanol and ethanol as acyl-acceptors.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…The abundant oxygen atoms that create hydroxyl, epoxide, carbonyl, and carboxyl functional groups on the GO surface are responsible for more hydrophilicity compared to the other graphene derivatives. 23 A three-dimensional GO (3DGO) has been provided for curcumin drug carrier. In this drug delivery system, PVA and sodium alginate (SA) act as hydrophile polymers for water soluble drug uptake, as well as crosslink agents for GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme lipase immobilised on magnetic nanoparticles is a proven technology for biodiesel from algal biomass. Nematian et al ( 2020 ), demonstrated biodiesel production from Chlorella vulgaris using a lipase immobilised nanoparticle catalyst and achieved a recovery rate of 71.9% biodiesel. The study highlighted the sensitivity and recyclability of the lipase-nanoparticle catalyst with a pronounced performance efficacy to over five times (70%) against the conventional methods.…”
Section: Systemic Exploration Of Recent Trends In Algal Biomass Valor...mentioning
confidence: 99%